ABOUT ONE APPROACH OF TESTING GEOMETRICAL KNOWLEDGE SYSTEM BUILDING (Journal of Information Technologies in Education (ITE), 2015)
The paper presents an approach to testing system building of procedural geometric knowledge, i.e. knowledge of basic computational formulas and skills to use them. This approach consists in constructing the mathematical models for each academic module in Geometry. The main constructing objects are the templates of tests which represent mathematical models of tests set in general terms. Template of similar tests class is represented by a geometric drawing, formula-correlations system binding the elements of the drawing, by templates of test conditions and template of response. Each such template is used both in generating algorithms of similar specific tests’ plurality and algorithms of automatic validation of responses’ correctness. The proposed method makes it possible to describe a relatively simple class of specific tests. An important feature of the system is the ability to automatically check not only the final answer, but the intermediate answer formulas. For the implementation of the testing system is necessary to use methods of computer algebra and algebraic programming technology.
Keywords: structural and logic schemes (SLS); test environment; test mathematical models; testing